A Survey of Escherichia coli and Salmonella in the Hyporheic Zone of a Subtropical Stream: Their Bacteriological, Physicochemical and Environmental Relationships - Mugnai, Riccardo (2015)
Universidade Federal do Rio de Janeiro. Museu Nacional. Departamento de Invertebrados. Laboratório de Aracnologia. Rio de Janeiro, RJ, Brasil.